Natural Treatment of Stormwater Runoff - Armentrout, Taz; Barbeau, Nicholas; Kincaid, Jordan; Phillips, Nathan; Pittore, Ephraim; Hunsucker III, James F.; Smith, James E. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
In the Northeastern region of the United States, there is a growing problem in the collection and treatment of stormwater runoff. In recent years the region has experienced record amounts of rainfall with the projections pointing to this trend continuing. The Sanitation Department in most of these areas is responsible for the collection of this stormwater, meaning that the runoff is combined with, and treated as wastewater. Most of the current water treatment systems cannot handle these increased demands during large storms and as result hundreds of thousands of gallons of waste are dumped into the surrounding rivers and streams during and shortly after these large storms. The US Environmental Protection Agency (EPA) is levying fines and promulgating additional regulations for these violations, so a long term solution is necessary. The proposed method of addressing these needs involves mimicking the natural water cycle which would naturally allow the water to be absorbed into the ground and then evaporated as opposed to flowing directly into the sanitation system. This study looked at a local urbanized region, Pittsburgh Pennsylvania, as a case study considering the locale and its urbanization, the current infra-structure, and the current and future requirements for storm water runoff mitigation. The study defined the problem, considered the current legal implications, and then looked at the types of technologies that could be implemented to address this problem. The technology ultimately recommended would be a roof spray technology that is capable of collecting the excess stormwater runoff, storing it, and then spraying it onto a roof where it would be evaporated. This system would reduce the excess water runoff created during storms that the sanitation systems cannot adequately handle. The concept for this runoff solution is provided with an analysis of the actual issues underlying these runoff problems.